Continuous flow preparation method of mercaptan-modified carbon-loaded gold nanoparticles

By introducing the thiol mixing and remixing stage in the continuous flow preparation method of carbon gold-carrying nanoparticles, the particle size and distribution of gold nanoparticles are accurately regulated, and the amount of precipitant is optimized through the monitoring stage, the problems of excessive particle size and uneven distribution in traditional methods are solved, and efficient industrial production is achieved.

CN119793453AActive Publication Date: 2025-04-11TIANJIN FEYNMAN POWER TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510289470.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

In the prior art, carbon gold-loaded nanoparticles have too large particle sizes and uneven distribution in amplified production, resulting in poor dispersion. The traditional batch method has complicated steps, making it difficult to achieve large-scale industrial production.

Method used

The continuous flow preparation method of carbon gold-carrying nanoparticles modified by thiol is used. By setting the thiol mixing stage and the remixing stage in the continuous flow production process, the particle size and distribution of gold nanoparticles are accurately controlled, and the amount of precipitant is accurately controlled through the monitoring stage to reduce intermediate redundancy steps, and the continuous production of products above 100 grams is achieved.

Benefits of technology

It improves the dispersion and stability of the catalyst, solves the problems of excessive particle size and uneven distribution, simplifies production steps, improves production efficiency, and has good industrial amplification potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793453A_ABST
    Figure CN119793453A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano material preparation, in particular to a mercaptan-modified carbon-loaded gold nanoparticle continuous flow preparation method, which comprises a reduction mixing stage, a mercaptan mixing stage, a carbon powder dispersing stage, a carbon powder loading stage, a back-mixing stage and a monitoring stage, the back-mixing stage is arranged between the mercaptan mixing stage and the carbon powder dispersing stage, and the monitoring stage is arranged after the carbon powder loading stage; by means of the technological process, continuous production of products of hectogram grade or above can be achieved, middle redundant steps are reduced, the good yield is guaranteed while the particle size and distribution of the gold nanoparticles are accurately regulated and controlled, and compared with the prior art, the problems that in amplified production of the carbon-loaded gold nanoparticles, the steps are complex and difficult to repeat, and the production cost is low are solved. The problems of poor product dispersity and stability and low yield caused by overlarge particle size, non-uniform distribution and easy agglomeration of the obtained product are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles. Background Art

[0002] Carbon-supported gold nanoparticles (AuNPs) catalysts have shown excellent catalytic performance in many chemical reactions and are widely used in organic synthesis, environmental governance, fuel cells, etc. Their excellent catalytic performance is attributed to the high surface energy and highly active surface of gold nanoparticles. Generally, loading gold nanoparticles on carbon materials can further improve their catalytic performance and stability.

[0003] At present, the methods for preparing carbon-supported gold nanoparticle catalysts are mainly divided into traditional intermittent methods and innovative continuous flow methods. Traditional intermittent methods generally include solution methods, chemical reduction methods, and precipitation methods. Although these methods are relatively mature, they usually have complicated steps and poor repeatability, making them difficult to carry out large-scale production, which limits their widespread application in industry.

[0004] Patent CN116672984A discloses a continuous and controllable synthesis method and microfluidic synthesis platform for carbon nanotube nanocomposites loaded with nano-metal particles. The method can precisely control the reaction conditions at the microscale and achieve uniform mixing of the reaction reagents within milliseconds. Rapid and efficient mixing can reduce the difference in residence time between the reaction reagents, thereby effectively improving the dispersibility and repeatability of the synthesized nanoparticles. However, the reaction flow rate is too small and is suitable for small-scale reactions.

[0005] A variety of organic stabilizing ligands, including phosphines, amines, and thiols, are often used to synthesize gold nanoparticles and regulate their surface properties. Among them, thiols are strongly adsorbed on the surface of gold nanoparticles during the synthesis process, minimizing the interaction of van der Waals forces between adjacent grains, and are widely used in regulating the particle size, distribution, and shape of monodisperse gold nanoparticles.

[0006] Patent CN116801978A discloses a gold-loaded carbon catalyst and a method for manufacturing the same, including a gold particle generation step, a processing step and a loading step. Although the size and distribution of the gold particles can be precisely controlled by adjusting the coverage of the alkanethiol ligand, reaction conditions and other parameters, the preparation method requires multiple steps and the conversion between steps is cumbersome, the reaction time is long, and it is not conducive to large-scale production. In addition, the synthesis of the gold-carbon catalyst requires the synthesis of gold nanoparticles in a solution first, and then the separation and washing of the gold nanoparticles. In the process, not only will the gold element be lost, but the gold nanoparticles will inevitably agglomerate, and the operation is complicated, which is not conducive to industrial scale-up.

[0007] At present, the selection of reducing agents and the control of reaction conditions in the process of continuous flow reaction loading onto carbon materials will affect the size and morphology of the final nanoparticles formed, and will inevitably lead to the agglomeration of gold nanoparticles. A method that can be precisely controlled is needed to improve the particle size and distribution in the industrial scale-up production of continuous flow reactions, so as to improve the dispersion and stability of the resulting gold nanocatalysts. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a continuous flow preparation method for thiol-modified carbon-supported gold nanoparticles. By adding ligands, the size and distribution of gold nanoparticles are effectively regulated, the storage time of the catalyst is further extended, and the continuous flow method is improved. It can achieve continuous production of products above 100 grams, reduce intermediate redundant steps, and accurately regulate the particle size and distribution of gold nanoparticles while ensuring good yield, which has good industrial scale-up potential.

[0009] A continuous flow preparation method for thiol-modified carbon-supported gold nanoparticles comprises the stages of reduction mixing→thiol mixing→carbon powder dispersion→carbon powder loading, and also comprises a back-mixing stage and a monitoring stage, wherein the back-mixing stage is arranged between the thiol mixing stage and the carbon powder dispersion stage, and the monitoring stage is arranged after the carbon powder loading stage; wherein the back-mixing stage is a process in which a primary mixed liquid flowing out of the thiol mixing stage is sent back to the thiol mixing stage through a back-mixing pipeline for re-mixing to obtain a re-mixed liquid; and the monitoring stage comprises a process of filtering a catalyst solution obtained in the carbon powder loading stage and monitoring the color change of the filtrate.

[0010] Furthermore, the volume of the initially mixed liquid sent back to the mercaptan mixing stage through the back-mixing pipeline for remixing is not less than one fifth of the total volume of the initially mixed liquid flowing out of the mercaptan mixing stage.

[0011] Furthermore, the flow rate of the solution in the reduction mixing stage, the thiol mixing stage and the carbon powder dispersion stage is 6-12 L / h.

[0012] Furthermore, the reduction and mixing stage is a process of mixing a gold salt solution with a reducing agent solution to obtain gold nanoparticles, the concentration of the gold salt solution is 18.00-22.75 mmol / L, and the concentration of the reducing agent solution is 23.40-27.90 mmol / L.

[0013] Furthermore, the thiol mixing stage is a process of mixing the thiol solution with the gold nanoparticles obtained in the reduction mixing stage to obtain a primary mixed solution, and the concentration of the thiol solution is 18.00-22.75 mmol / L.

[0014] Furthermore, the carbon powder dispersion stage is a process in which the primary mixed liquid obtained in the thiol mixing stage and the remixed liquid obtained in the back mixing stage are added to the carbon powder dispersion liquid and mixed to obtain the carbon powder dispersion mixed liquid, and the concentration of the carbon powder dispersion liquid is 13.40-17.20 g / L.

[0015] Furthermore, the carbon powder loading stage is a process of adding a sedimentation agent to the carbon powder dispersion mixture obtained in the carbon powder dispersion stage to load the gold nanoparticles with carbon powder, and the flow rate of the sedimentation agent is 1-7 L / h and the residence time is 2-5 min.

[0016] Furthermore, the completeness of the carbon powder loading can be determined based on the color of the filtrate in the monitoring stage, and the flow rate of the sedimentation agent can be adjusted accordingly.

[0017] Furthermore, the gold salt in the reduction mixing stage includes tetrahydrate chloroauric acid and trihydrate chloroauric acid, and the reducing agent includes any one of tert-butylamine borane, dimethylamine borane and morpholine borane.

[0018] Furthermore, the mercaptan in the mercaptan mixing stage includes any one of n-dodecyl mercaptan, n-hexyl mercaptan, n-octyl mercaptan, n-decapryl mercaptan and n-hexadecyl mercaptan.

[0019] Furthermore, the sedimentation agent in the carbon powder loading stage is anhydrous ethanol or methanol.

[0020] Furthermore, the solvent used in the reduction mixing stage and the mercaptan mixing stage is a mixed solution of n-hexane and oleylamine, and the volume ratio of n-hexane to oleylamine is 1.5-1:1.

[0021] Furthermore, the temperature of the reduction mixing stage and the mercaptan mixing stage is 25-40°C.

[0022] Furthermore, the solvent used in the carbon powder dispersion stage is anhydrous ethanol or methanol.

[0023] Furthermore, the toner dispersion to be added in the toner dispersion stage needs to be continuously stirred.

[0024] The advantages of the present invention are: 1. The present invention can improve production efficiency by using a continuous flow method. By continuously flowing reactants into the reaction system and performing rapid reactions and product separation, continuous production can be achieved, intermediate redundant steps can be reduced, and the present invention has good industrial amplification potential. The present invention can achieve continuous production of products above 100 grams while ensuring a good yield. Compared with the prior art, the present invention can solve the technical problems of complex steps, difficulty in repeating, and low yield of the obtained products in amplified production; 2. The present invention provides a thiol mixing stage and a back-mixing stage in the continuous flow production process. The addition of thiol can accurately control the particle size and distribution of gold nanoparticles. The back-mixing stage can fully mix and age the thiol and gold nanoparticle solution to achieve a narrow size distribution of the gold nanoparticles, thereby improving the dispersibility and stability of the catalyst, and solving the problem of poor dispersibility of carbon-supported gold nanoparticles in the prior art due to excessive particle size and uneven distribution in the scale-up production. 3. The present invention sets a monitoring stage in the continuous flow production process, and determines whether the carbon powder loading is complete by filtering the color of the gold-carbon catalyst solution, thereby accurately controlling the amount of precipitant. Compared with the existing carbon-supported gold nanoparticle scale-up production process, it can avoid the problem of gold nanoparticle agglomeration and increased production particle size caused by excessive use of precipitant. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a process flow chart of a continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles of the present invention; Figure 2 It is a schematic diagram of the pipeline connection of the continuous flow platform constructed by the present invention; Figure 3 is an X-ray diffraction spectrum of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 1 of the present invention; Figure 4 is a transmission electron microscope image of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 1 of the present invention; Figure 5 is an X-ray diffraction spectrum of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 2 of the present invention; Figure 6 is a transmission electron microscope image of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 2 of the present invention; Figure 7 is an X-ray diffraction spectrum of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 3 of the present invention; Figure 8 is a transmission electron microscope image of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 3 of the present invention; Fig. 9 is an X-ray diffraction spectrum of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 4 of the present invention; Fig.10 is a transmission electron microscope image of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 4 of the present invention; Fig.11 is the X-ray diffraction spectrum of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 5 of the present invention; Fig.12is a transmission electron microscope image of the thiol-modified carbon-supported gold nanoparticle catalyst obtained in Example 5 of the present invention; Fig.13 is an X-ray diffraction spectrum of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 1 of the present invention; Fig.14 is a transmission electron microscope image of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 1 of the present invention; Fig.15 is the X-ray diffraction spectrum of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 2 of the present invention; Fig.16 is a transmission electron microscope image of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 2 of the present invention; Fig.17 is an X-ray diffraction spectrum of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 3 of the present invention; Fig.18 is a transmission electron microscope image of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 3 of the present invention; Fig.19 is an X-ray diffraction spectrum of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 4 of the present invention; Fig. 20 It is a transmission electron microscope image of the carbon-supported gold nanoparticle catalyst obtained in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.

[0027] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation will be given.

[0028] Example 1 This example provides a continuous flow preparation method for thiol-modified carbon-supported gold nanoparticles. First, a raw material solution is prepared: A mixed solution is prepared with n-hexane: oleylamine = 1:1 ratio (volume ratio) as solvent; chloroauric acid solution, reducing agent solution and thiol solution are prepared with trihydrate chloroauric acid, tert-butylamine borane and n-dodecyl mercaptan as solutes respectively for later use; a carbon powder dispersion is prepared with anhydrous ethanol as solvent for later use; and anhydrous ethanol is used as a precipitant for later use; The prepared raw material solution is then fed into a continuous flow platform for the preparation of thiol-modified carbon-supported gold nanoparticles. The preparation process is as follows: Figure 1 As shown, it includes reduction mixing → mercaptan mixing → back mixing → carbon powder dispersion → carbon powder loading → monitoring stage, and the specific steps are as follows: Reduction and mixing stage: The gold salt solution and the reducing agent solution are driven by a peristaltic pump to flow out of the raw material container and into the first mixing tube through the connecting pipe for mixing. The concentration of the gold salt solution is 18 mmol / L, the flow rate is 6 L / h, the concentration of the reducing agent solution is 23.4 mmol / L, the flow rate is 6 L / h, and the temperature is 25°C. The reduction reaction begins, and the reducing agent in the reducing agent solution converts the Au in the gold salt solution to 3+ The ions are reduced to zero-valent gold to obtain gold nanoparticles; Thiol mixing stage: The thiol solution is driven by a peristaltic pump to flow out of the raw material container through a connecting tube and sent into a second mixing tube together with the gold nanoparticles flowing out of the reduction mixing stage in step (1) to obtain a primary mixed solution. The mixing temperature is 25°C, the concentration of the thiol solution is 18 mmol / L, and the flow rate is 6 L / h.

[0029] (3) Back-mixing stage: A back-mixing tube is connected to the outlet of the second mixing tube. 1 / 5 (volume) of the initial mixed liquid flowing out of the outlet of the second mixing tube flows into the next stage. 4 / 5 (volume) of the initial mixed liquid flowing out of the outlet of the second mixing tube flows back to the inlet of the second mixing tube through the back-mixing tube and flows into the second mixing tube again with the continuously flowing thiol solution to mix with the re-mixed liquid. After a period of time, the narrow size distribution of gold nanoparticles is achieved through Oswald ripening. (4) Carbon powder dispersion stage: The carbon powder dispersion liquid driven by the peristaltic pump flows out from the raw material container through the connecting pipe and is mixed with 1 / 5 of the primary mixed liquid and 4 / 5 of the remixed liquid to flow into the third mixing tube to obtain a carbon powder dispersion mixed liquid. The concentration of the carbon powder dispersion liquid is 17.20 g / L and the flow rate is 12 L / h.

[0030] (5) Carbon powder loading stage: The precipitant driven by the peristaltic pump flows out from the raw material container through the connecting pipe and flows into the fourth mixing tube together with the carbon powder dispersion mixed liquid to obtain a thiol-modified carbon-supported gold nanoparticle catalyst solution. The flow rate of the precipitant is controlled between 1-7 L / h, and the residence time is 5 min. (6) Monitoring stage: The obtained thiol-modified carbon-supported gold nanoparticle catalyst solution is filtered through a needle filter, and the color of the obtained filtrate is monitored to see if it is obviously red. If so, it means that the gold nanoparticles are not fully loaded, and the flow rate of the precipitant is appropriately adjusted. The sample 5 minutes before the reaction is additionally processed. After 5 minutes of reaction, the catalyst solution basically meets the requirements of the particle size distribution.

[0031] The production scale of this embodiment is 250g / day, and the yield is 87%.

[0032] The pipeline connection diagram of the continuous flow platform constructed in this embodiment is as follows Figure 2 As shown, it includes five raw material containers, a peristaltic pump, a first mixing tube, a second mixing tube, a third mixing tube, a fourth mixing tube, a back-mixing tube, a needle filter and a product container in sequence, wherein the raw material containers of the gold salt solution, the reducing agent solution, the thiol solution and the carbon powder dispersion are all connected to the inlet of the first peristaltic pump. Because the flow rates are inconsistent, the raw material container of the sedimentation agent is connected to the inlet of the second peristaltic pump. The outlets of the first peristaltic pump and the second peristaltic pump are connected to the flow meter. The first mixing tube, the second mixing tube, the third mixing tube and the fourth mixing tube are located between the flow meter and the product container. , a connecting pipe is provided between each mixing tube, and the flow meter, mixing tube and product container are all connected through the connecting pipe, and the mixing tube and the connecting pipe are connected through a three-way joint, wherein the outlet of the fourth mixing tube and two pipelines are connected to the two ends of the three-way joint, one of which is connected to one end of the upper valve, and the other end is connected to the first pipeline, and then the first pipeline is connected to the needle filter, and a transparent reagent bottle is placed at the outlet of the filter to observe the color of the filtrate, and the other of the two pipelines is connected to one end of the lower valve, and the other end is connected to the second pipeline, and then the second pipeline is connected to the product container. The raw material solution of the carbon-supported gold nanoparticle catalyst is prepared, and it flows out continuously from five raw material solution containers under the pressure of a peristaltic pump, and then after being regulated by a flow meter, the first mixing tube, the second mixing tube, the third mixing tube, and the fourth mixing tube are used to complete the mixing reaction in turn through the reduction mixing → thiol mixing → back mixing → carbon powder dispersion → carbon powder loading → monitoring stage.

[0033] The connecting pipe in this embodiment is a PTFE pipe.

[0034] The mixing tube in this embodiment adopts a static mixer, and the internal design has spiral blades, corrugated plates and other structures, which can effectively disrupt the laminar flow of the fluid and promote mixing, so as to speed up the reaction process and improve the reaction efficiency.

[0035] In the present embodiment, an agitator is provided in the raw material container of the toner dispersion. The agitator is vertically mounted at the top outlet of the raw material container of the toner dispersion. The stirring end of the agitator extends into the raw material container of the toner dispersion to stir the toner dispersion to prevent the toner dispersion from settling when left standing, resulting in inconsistent toner concentrations at the top and bottom of the dispersion.

[0036] In this embodiment, small temperature sensors are installed on the side walls of the first mixing tube, the second mixing tube, the third mixing tube and the fourth mixing tube to monitor temperature changes in real time and take measures to maintain the temperature to ensure that the reaction is carried out at the optimal temperature, thereby improving the reaction selectivity and product quality.

[0037] Characterization analysis: The product obtained in this example was subjected to XRD test, and the test spectrum was as follows Figure 3 As shown, XRD confirmed that the product crystal structure was Au / C and the catalyst particle size was 1.7 nm.

[0038] The calculation formula of catalyst crystal size is:

[0039] Where d is the grain size (nm), which indicates the average thickness of the grain in the direction perpendicular to the (hkl) crystal plane. λ is the wavelength of the incident X-ray (here 1.54056Å), and θ is the incident angle of the X-ray on the crystal plane. B is the half-height width of the measured sample diffraction peak, which needs to be converted into radians (rad) during the calculation process after double-line correction and instrument factor correction.

[0040] The product obtained in this example was subjected to TEM test, and the TEM image is as follows Figure 4 As shown, it can be seen that the obtained thiol-modified carbon-supported gold nanoparticles have a narrow size distribution at 200 nm, the particles are of the same size, are evenly distributed, have no obvious agglomeration phenomenon, and have high dispersibility.

[0041] Example 2 The preparation method of this example is the same as that of Example 1, except that the parameter conditions in the process are different, as follows: In this embodiment, a mixed solution is prepared with a ratio of n-hexane: oleylamine = 1.5:1 (volume ratio) as solvent; chloroauric acid tetrahydrate, dimethylamine borane, and n-hexadecyl mercaptan are used as solutes to prepare chloroauric acid solution, reducing agent solution, and mercaptan solution for standby use; methanol is used as solvent to prepare a carbon powder dispersion for standby use; methanol is used as a precipitant for standby use; In this embodiment, the temperature of the reduction mixing stage is 40° C., the concentration of the gold salt solution is 22.75 mmol / L, the flow rate is 12 L / h, and the concentration of the reducing agent solution is 27.90 mmol / L, the flow rate is 12 L / h.

[0042] In this embodiment, the temperature of the mercaptan mixing stage is 40° C., the concentration of the mercaptan solution is 22.75 mmol / L, and the flow rate is 12 L / h.

[0043] In the toner dispersion stage of this embodiment, the concentration of the toner dispersion is 17.20 g / L, and the flow rate is 12 L / h.

[0044] The flow rate of the sedimentation agent in this embodiment is controlled between 1-7 L / h, and the residence time is 2 min; The production scale of this embodiment is 350g / day, and the yield is 83%.

[0045] Characterization analysis: The product obtained in this example was also subjected to XRD and TEM tests. The test method and particle size calculation method were the same as in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this example was Au / C, and the catalyst particle size was 2.3 nm (the test spectrum is shown in FIG. Figure 5 As shown in the figure), the TEM results show that the catalyst product particles are evenly distributed, with no obvious agglomeration and high dispersion (TEM image as shown in the figure). Figure 6 as shown).

[0046] Example 3 The preparation method of this example is the same as that of Example 1, except that the parameter conditions in the process are different. In this example, the flow rate of the solution in the reduction mixing stage, the thiol mixing stage, and the carbon powder dispersion stage is 15 L / h.

[0047] Characterization analysis: The product obtained in this example was also subjected to XRD and TEM tests. The test method and particle size calculation method were the same as in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this example was Au / C, and the catalyst particle size was 4.6 nm (the test spectrum is shown in FIG. Figure 7 As shown in the figure, the TEM test showed that the catalyst particles were unevenly distributed and partially agglomerated. This was because the flow rate was too fast, which led to unstable flow of the peristaltic pump, uneven mixing and insufficient mixing (TEM image as shown in the figure). Figure 8 as shown).

[0048] The production scale of this embodiment is 200g / day, and the yield is 85%.

[0049] Example 4 The preparation method of this example is the same as that of Example 1, except that the parameter conditions in the process are different. In this example, the flow rate of the solution in the reduction mixing stage, the thiol mixing stage, and the carbon powder dispersion stage is 4 L / h.

[0050] Characterization analysis: The product obtained in this example was also subjected to XRD and TEM tests. The test method and particle size calculation method were the same as in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this example was Au / C, and the catalyst particle size was 3.4 nm (the test spectrum is shown in FIG. Fig. 9 As shown in the figure), the TEM test showed that the particle distribution of the obtained catalyst product was relatively uneven, and there was some agglomeration. This was because the flow rate of the peristaltic pump was unstable due to the slow flow rate, and some mixing was uneven (TEM image as shown in the figure). Fig.10 as shown).

[0051] The production scale of this embodiment is 250g / day, and the yield is 83%.

[0052] Example 5 The preparation method of this example is the same as that of Example 1, except that the parameter conditions in the process are different, as follows: In this embodiment, the concentration of the gold salt solution is 30 mmol / L, the concentration of the reducing agent solution is 15 mmol / L, the concentration of the thiol solution is 10 mmol / L, and the concentration of the carbon powder dispersion is 20 g / L.

[0053] Characterization analysis: The product obtained in this example was also subjected to XRD and TEM tests. The test method and particle size calculation method were the same as in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this example was Au / C, and the catalyst particle size was 3.9 nm (the test spectrum is shown in FIG. Fig.11 As shown in the figure), the TEM test showed that the particle distribution of the catalyst product was very uneven, the particle size was relatively large, and there was obvious agglomeration in some parts (TEM image as shown in the figure). Fig.12 as shown).

[0054] The production scale of this embodiment is 300g / day, and the yield is 80%.

[0055] Comparative Example 1 This comparative example adopts the traditional intermittent method to prepare carbon-supported gold nanoparticles, and the preparation process is as follows: (1) Prepare solution A (6.176 g chloroauric acid + 450 mL oleylamine + 450 mL n-hexane, stir and mix in argon for 20 min) and solution B (1304.4 mg TBAB (borane-tert-butylamine) + 50 mL oleylamine + 50 mL n-hexane, mix by ultrasonication) and set aside; (2) Reduction: Under stirring, add solution B to solution A quickly, and react at room temperature for 1 h under argon protection. Add a small amount of cyclohexane to the product (to clean the flask wall), transfer it to a centrifuge tube, add anhydrous ethanol (cyclohexane: anhydrous ethanol = 1:4), and directly centrifuge and wash three times to obtain gold nanoparticle solids. (3) Dispersing carbon powder and loading: According to the required loading, weigh a certain amount of carbon powder, and prepare the amount of cyclohexane according to the ratio of 6 mg carbon powder to 2 mL cyclohexane. First, take half of the cyclohexane and mix it with the carbon powder. Ultrasonic mixing is carried out for 10 min. Then, the remaining cyclohexane is used to dissolve the gold nanoparticles and transfer them to a round-bottom flask. While stirring, add the carbon powder dispersion and stir overnight at room temperature for 12 h. (4) Separation and washing: After stirring, let it stand for half an hour until the product is completely settled. Use a pipette to transfer the upper clear liquid and pour the lower product into a centrifuge tube. Centrifuge and wash three times. Vacuum dry at 60°C. Collect the sample and grind it to obtain a solid powder.

[0056] Characterization analysis: The product obtained in this comparative example was also subjected to XRD and TEM tests. The test method and the method for calculating the particle size were the same as those in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this comparative example was Au / C (the XRD test spectrum is shown in FIG. Fig.13 The catalyst particle size is 6.7 nm. Fig.14 As shown, it can be seen that the conventional intermittent method for preparing carbon-supported gold nanoparticles has a large particle size at 200 nm, an uneven particle size distribution, and some particles show obvious agglomeration.

[0057] The maximum reaction amount of this comparative example is 20g, and the yield is 70%.

[0058] Comparative Example 2 The preparation method of this comparative example is the same as that of Example 1, except that this comparative example does not set a back-mixing stage. After the thiol and gold nanoparticles are mixed in the thiol mixing stage, the obtained mixed liquid directly flows into the carbon powder dispersion stage to be mixed with the carbon powder dispersion.

[0059] The product obtained in this comparative example was also subjected to XRD test and TEM test. The test method and the method for calculating the particle size were the same as those in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this comparative example was Au / C, and the catalyst particle size was 3.5 nm (the test spectrum is shown in FIG. Fig.15 As shown in the figure, the TEM results show that the gold nanoparticles of the catalyst are large in size, with uneven particle size distribution and a small amount of agglomeration of gold nanoparticles (TEM image as shown in the figure). Fig.16 as shown).

[0060] The production scale of this comparative example is 200 g / day, and the yield is 75%.

[0061] Comparative Example 3 The preparation method of this comparative example is the same as that of Example 1, except that the thiol modification stage and the back-mixing stage are not set in this comparative example, and the gold nanoparticles obtained in the reduction stage directly flow into the carbon powder dispersion stage and are mixed with the carbon powder dispersion liquid.

[0062] The product obtained in this comparative example was also subjected to XRD and TEM tests. The test method and the method for calculating the particle size were the same as those in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this comparative example was Au / C, and the average size of the catalyst particles was 4.5 nm (the test spectrum is shown in FIG. Fig.17 As shown in the figure), the TEM results show that the particle distribution range of the obtained catalyst product is wide and uneven, the particle sizes are different, and there is obvious agglomeration in some parts (TEM image as shown in the figure) Fig.18 as shown).

[0063] The production scale of this comparative example is 200 g / day, and the yield is 80%.

[0064] Comparative Example 4 The preparation method of this comparative example is the same as that of Example 1, except that this comparative example does not set a monitoring stage, and the dispersion flowing out of the carbon powder dispersion stage flows into the carbon powder loading stage together with the sedimentation agent, and the carbon-supported gold nanocatalyst solution obtained after staying for 5 minutes directly flows into the product solvent for collection.

[0065] The product obtained in this comparative example was also subjected to XRD and TEM tests. The test method and the method for calculating the particle size were the same as those in Example 1. XRD confirmed that the crystal structure of the catalyst product obtained in this comparative example was Au / C, and the average size of the catalyst particles was 4.0 nm (the test spectrum is shown in FIG. Fig.19 As shown in the figure, the TEM image shows that the catalyst product particles show obvious agglomeration (TEM image as shown in the figure). Fig. 20 as shown).

[0066] The production scale of this embodiment is 200g / day, and the yield is 77%.

[0067] The results of Example 1 and Comparative Example 1 show that the method of the present application has simple steps and is suitable for continuous production of products above 100 grams, while ensuring a good yield of up to 87%, while the maximum reaction magnitude of the method of Comparative Example 1 is only 20g, and the yield is 70%. It can be seen from the catalyst particle size and dispersion results of Examples 1-5 and Comparative Examples 2-4 that the present invention can accurately regulate the particle size and distribution of gold nanoparticles by setting a mercaptan mixing stage and a back-mixing stage in a continuous flow production process, and the addition of mercaptan can fully mix and age the mercaptan and gold nanoparticle solution, thereby achieving a narrow size distribution of gold nanoparticles, thereby improving the dispersibility and stability of the catalyst, and the regulation of the sedimentation agent in the monitoring stage can improve the agglomeration phenomenon.

[0068] For those skilled in the art, the invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any reference numerals in the claims should not be regarded as limiting the claims involved.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.

Claims

1. A continuous flow preparation method for thiol-modified carbon-supported gold nanoparticles, comprising reduction mixing → thiol mixing → carbon powder dispersion → carbon powder loading stages, characterized in that: It also includes a back-mixing stage and a monitoring stage, wherein the back-mixing stage is arranged between the mercaptan mixing stage and the carbon powder dispersion stage, and the monitoring stage is arranged after the carbon powder loading stage; wherein the back-mixing stage is a process in which the primary mixed liquid flowing out of the mercaptan mixing stage is sent back to the mercaptan mixing stage through a back-mixing pipeline to be mixed again to obtain a remixed liquid; and the monitoring stage includes a process of filtering the catalyst solution obtained in the carbon powder loading stage and monitoring the color change of the filtrate.

2. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1, characterized in that: The flow rate of the solution in the reduction mixing stage, the thiol mixing stage and the carbon powder dispersion stage is 6-12 L / h.

3. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1, characterized in that: The volume of the initially mixed liquid sent back to the mercaptan mixing stage through the back-mixing pipeline for remixing is not less than one fifth of the total volume of the initially mixed liquid flowing out of the mercaptan mixing stage.

4. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1 or 2, characterized in that: The reduction and mixing stage is a process of mixing a gold salt solution with a reducing agent solution to obtain gold nanoparticles. The concentration of the gold salt solution is 18.00-22.75 mmol / L, and the concentration of the reducing agent solution is 23.40-27.90 mmol / L.

5. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1 or 2, characterized in that: The thiol mixing stage is a process of mixing the thiol solution with the gold nanoparticles obtained in the reduction mixing stage to obtain a primary mixed solution, and the concentration of the thiol solution is 18.00-22.75 mmol / L.

6. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1 or 2, characterized in that: The carbon powder dispersion stage is a process in which the primary mixed liquid obtained in the thiol mixing stage and the remixed liquid obtained in the backmixing stage are added to the carbon powder dispersion liquid to obtain a carbon powder dispersion mixed liquid. The concentration of the carbon powder dispersion liquid is 13.40-17.20 g / L.

7. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1 or 2, characterized in that: The carbon powder loading stage is a process in which a precipitant is added to the carbon powder dispersion mixture obtained in the carbon powder dispersion stage to load the gold nanoparticles with carbon powder. The flow rate of the precipitant is 1-7 L / h and the residence time is 2-5 min. The flow rate of the precipitant is regulated according to the color of the filtrate in the monitoring stage.

8. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 1 or 2, characterized in that: The gold salt in the reduction mixing stage includes tetrahydrate chloroauric acid and trihydrate chloroauric acid, and the reducing agent includes any one of tert-butylamine borane, dimethylamine borane, and morpholine borane; the thiol in the thiol mixing stage includes any one of n-dodecyl mercaptan, n-hexyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, and n-hexadecyl mercaptan, and the precipitant in the carbon powder loading stage is anhydrous ethanol or methanol.

9. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 8, characterized in that: The solvent used in the reduction mixing stage and the mercaptan mixing stage is a mixed solution of n-hexane and oleylamine, the volume ratio of n-hexane to oleylamine is 1.5-1:1, and the temperature of the system is 25-40°C.

10. The continuous flow preparation method of thiol-modified carbon-supported gold nanoparticles according to claim 6, characterized in that: The toner dispersion to be added in the toner dispersion stage needs to be continuously stirred, and the solvent of the toner dispersion is anhydrous ethanol or methanol.

Citation Information

Patent Citations

  • Thermochromic materials of the plasma absorption type, process for their preparation, and their applications

    EP1621574A1

  • Heterogeneous hydrosilylation catalysts, polymers formed therewith, and related coating compositions

    US20090018301A1

  • Process for recovering metal

    US20190292627A1

  • Process for making supported gold NP catalyst for the production of methyl methacrylate by oxidation esterification, catalyst obtained thereby and process of said oe

    WO2024123527A1